2014
DOI: 10.1111/1475-6773.12259
|View full text |Cite
|
Sign up to set email alerts
|

End-of-Life Medical Costs of Medicaid Cancer Patients

Abstract: Medicaid cancer patients incur substantially higher EOL costs than noncancer patients. This increased cost may reflect the cost of palliative care. Future studies should assess the types and timing of services provided to Medicaid cancer patients at the EOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 48 publications
1
30
0
Order By: Relevance
“…Consistent with the literature, our study identified (a) facilitative determinants of increased EOL care expenditures as male gender , younger age , being married , diagnosis with hematological malignancies, esophageal, colorectal, and head and neck cancer , and dying within 7–12 months of diagnosis , with (b) the impeding determinant as diagnosis with hepatic‐pancreatic cancer . We also found that death within 6 months of diagnosis was associated with lower EOL care expenditures, suggesting that these patients were relatively healthy until they were diagnosed with an aggressive malignancy.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Consistent with the literature, our study identified (a) facilitative determinants of increased EOL care expenditures as male gender , younger age , being married , diagnosis with hematological malignancies, esophageal, colorectal, and head and neck cancer , and dying within 7–12 months of diagnosis , with (b) the impeding determinant as diagnosis with hepatic‐pancreatic cancer . We also found that death within 6 months of diagnosis was associated with lower EOL care expenditures, suggesting that these patients were relatively healthy until they were diagnosed with an aggressive malignancy.…”
Section: Discussionsupporting
confidence: 88%
“…However, until recently, only ten studies worldwide had explored EOL care expenditures for cancer decedents . A 2016 study compared hospital expenditures using only single‐year data from six non‐U.S.…”
Section: Introductionmentioning
confidence: 99%
“…At the end of life, annual costs were 2 or 3 times higher than those in the initial phase, as reported by Mariotto et al; and net monthly costs ranged from approximately $4500 to $9000, depending on stage, as reported by Banegas et al (Table ) . For Medicaid populations in Georgia and Illinois, net costs were $9814 for the 4 months before death (2003 US dollars) …”
Section: Resultsmentioning
confidence: 55%
“…1 Healthcare spending at the end of life among patients with cancer diagnoses far exceeds that of those without cancer. 2 Even among patients with cancer, those who die “from cancer” have higher healthcare expenditures at the end of life than those who die from causes of death other than cancer. 3 End of life discussions have been associated with lower cost at the end of life.…”
Section: Introductionmentioning
confidence: 99%